2020
DOI: 10.1093/infdis/jiaa492
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus (HCV) Eradication With Interferon-Free Direct-Acting Antiviral-Based Therapy Results in KLRG1+ HCV-Specific Memory Natural Killer Cells

Abstract: Direct acting antiviral therapies rapidly clear chronic hepatitis C virus (HCV) infection and restore natural killer (NK) cell function. We investigated NK cell memory formation following HCV clearance by examining NK cell phenotype and responses from control and chronic HCV patients before and after therapy following sustained virologic response at 12 weeks post-therapy (SVR12). NK cell phenotype at SVR12 differed significantly from paired pre-treatment samples, with an increase in maturation markers CD16, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Consistent with these observations, a recent study of HCMV seropositive patients reported that high frequencies of adaptive CD57 + FcεR1γ − NK cells and elevated expression of PD‐1 were associated with high viral load in chronic HCV infection and were reduced after direct‐acting antiviral therapy (DAA) 57 . In a separate study, chronic HCV infection was similarly associated with higher frequencies of CD57 + and PD‐1 + NK cells compared to uninfected control individuals 58 . However, although PD1 expression frequency reduced after DAA, proportions of CD57 + and KLRG1 + cells increased after treatment, suggesting ongoing expansion of highly differentiated NK cells 58 .…”
Section: The Role Of Other Pathogens In Nk Cell Differentiationmentioning
confidence: 62%
See 3 more Smart Citations
“…Consistent with these observations, a recent study of HCMV seropositive patients reported that high frequencies of adaptive CD57 + FcεR1γ − NK cells and elevated expression of PD‐1 were associated with high viral load in chronic HCV infection and were reduced after direct‐acting antiviral therapy (DAA) 57 . In a separate study, chronic HCV infection was similarly associated with higher frequencies of CD57 + and PD‐1 + NK cells compared to uninfected control individuals 58 . However, although PD1 expression frequency reduced after DAA, proportions of CD57 + and KLRG1 + cells increased after treatment, suggesting ongoing expansion of highly differentiated NK cells 58 .…”
Section: The Role Of Other Pathogens In Nk Cell Differentiationmentioning
confidence: 62%
“…58 The slightly different NK cell outcomes in these two studies may be explained by differences in HCMV status, HCV viral genotype, viral load and treatment regimen. 57,58…”
Section: The Role Of Other Pathogens In Nk Cell Differentiationmentioning
confidence: 96%
See 2 more Smart Citations
“…These agents also have a favorable side effect profile, and their administration periods are shorter than those of their traditional counterparts. Despite a nearly 100% cure rate, DAA therapy does not prevent HCV reinfection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%